Measurement of solution parameters on sonication decellularization treatment - Noor Azmi, Azran Azhim; K.S. , Furukawa; M., Shafiq,; Y., Morimoto; T., Ushida (2014)
We have developed a sonication decellularization system to decellularized biological scaffolds in short time by combining sonication and chemical method. The aim of this study is to investigate decellularization efficiency on the different treated solution parameters. As a result, decreasing of dissolved oxygen (DO) would increase the conductivity and pH of decellularization solution, and decreasing of pH would increase conductivity. We found that the solution concentrationhas relation to its parameters and may influence the efficiency of sonication decellularization treatment.